ANALISIS YURIDIS KEPAILITAN BUMN PERSERO DIKAITKAN DENGAN PRINSIP PERLINDUNGAN HAK-HAK KREDITUR - Zikri Afdal; Firdaus Firdaus; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
In the Bankruptcy Law Number 37 of 2004, it has been regulated that business entities which cannot be automatically filed for bankruptcy such as securities companies, insurance companies, banks and SOEs. But regarding the bankruptcy of a SOEs has caused debate, especially regarding the bankruptcy of a SOEs. In the current SOE bankruptcy arrangement it is as if stating that SOEs cannot be declared bankrupt other than by the Minister of Finance, which is seen based on whether or not the company's capital is divided into shares as well as the disharmony of the SOE's definition of moving in the public interest with SOE's definition of SOEs in the The bankruptcy law and Act Number 19 of 2003 concerning SOEs and inconsistencies in understanding regarding whether or not SOEs was declared bankrupt under Law 17 of 2003 concerning State Finance, Law Number 1 of 2004 concerning State Treasury and Limited Company Law Number 40 of 2007. This legal disharmony creates legal uncertainty, thus potentially damaging the rights of creditors in the state bankruptcy case of SOEs.This thesis uses the normative legal research method with the scope of SOE bankruptcy, analysis of SOE bankruptcy arrangements, principles of bankruptcy through secondary data sources in the form of primary, secondary and tertiary legal materials with qualitative analysis by drawing deductive conclusions.Keyword: Bankcruptcy, SOEs, State finances